(untitled) (Journal of Dhaka Medical College, 2010)
Objectives: Globally about 15.5% of all births are born with low birth weight (LBW) and in Bangladesh, LBW rate is quite high. The present study was conducted to determine the socioeconomic and nutritional factors affecting LBW in urban community of Bangladesh. Methods: This case control study was done at Department of Obstetrics & Gynaecology of Shaheed Suhrawardy Medical College Hospital, Dhaka. Normally delivered singleton live births babies from January 2003 to January 2005 were selected purposively and after enrollment all newborns birth weight was measured. Then from the total (N=583) study populations childmother pairs formed and were divided in LBW group (n=135) and NBW group (n=448). Data were collected regarding maternal socioeconomic and nutritional factors by interviewing the mothers and family members. Variables were analyzed to find out significant maternal factors affecting LBW. Results: The LBW incidences in this study was found 23.2%. And 51.1% of the LBW came from the mother of <20year of age group, 50% mothers of LBW were found illiterate, socioeconomic status was significantly more poor, maternal anaemia was found significantly more common in LBW and iron & vitamin supplementation during pregnancy were found significantly less among the mothers of LBW babies in comparison to NBW. Significant relationship was found between early maternal age, poor educational and socioeconomic status, anaemia, iron & vitamin supplementation during pregnancy with LBW. No relationship was found between LBW and maternal height but significant relationship was found with maternal weight and BMI. Conclusion: These findings suggest that selectively targeted interventions such as delay age at first pregnancy (at >20 year of age), improving maternal education and nutrition, iron and vitamin supplementation can prevent LBW in Bangladesh.. Key words: LBW (Low Birth Weight); NBW (Normal Birth Weight); IUGR(intrauterine growth retardation). DOI: 10.3329/jdmc.v17i2.6588 J Dhaka Med Coll. 2008; 17(2) : 83-87